Evaluation of insecticides for their field efficacy against turnip aphid, Lipaphis erysimi (Kaltenbach) on Indian mustard (Journal of Oilseed Brassica, 2026)
A field study was carried out to evaluate the field efficacy of some insecticides against turnip aphid (Lipaphis erysimi) on Indian mustard (Brassica juncea L.). Different treatments were found effective in reducing the aphid population but with variable efficacy. Among them, the spray of thiamethoxam 25 WG @ 0.2 g/ litre water was found to be best treatment followed by imidacloprid 17.8 SL @ 0.25 ml/litre water over check. Thus, for effective management of turnip aphid, crop can be sprayed with either of these insecticides whenever the aphid population reaches economic threshold level.